Cutis marmorata telangiectatica congenita on hand and forearm: Initial and follow-up observations of a rare case - Cemre Büşra Türk; Dilara İlhan; Ozan Erdem; Mehmet Salih Gürel; Ayşe Esra Koku Aksu (Galenos Publishing House, 2022)
Cutis marmorata telangiectatica congenita (CMTC) is a rare, benign, cutaneous vascular anomaly usually located on lower limbs. It regresses spontaneously in time and sometimes may be seen with accompanying abnormalities. We present a 2-months-old girl with CMTC on hand and arm and no improvement in her 4-years follow-up period. Furthermore, we review CMTC's clinical features, evaluate the differential diagnosis approach, and emphasize the necessity of long-term follow-up accompanied by literature.